Analyzing of Religious and Cultural Conflicts in West Java - Syifa Khairin (Green Publisher Indonesia, 2026)
Indonesia is a country with a diversity of ethnicities, cultures, races, and religions, which reflects the principle of Bhinneka Tunggal Ika. Although this diversity is a source of harmony, social and religious-based conflicts are inevitable, as seen in the cases in West Java. This paper explores the role of the Religious Harmony Forum (FKUB) as a mediator in resolving religious conflicts. Using the conflict cycle framework, this paper analyzes the dynamics of conflict, starting from the basis of conflict to its resolution. This research highlights the challenges of FKUB in maintaining neutrality, limited authority, and the importance of the government's role in creating policies that support religious harmony. Short, medium, and long-term action plans are formulated to strengthen the role of FKUB, enhance interfaith dialogue, and build a network of cooperation with various related parties. The conclusion shows that strengthening FKUB and tolerance education are key steps to encourage the sustainability of peace in society.